Differential Processing of Propeptide Inhibitors of Rap Phosphatases in Bacillus subtilis - Jiang, Min (American Society for Microbiology, 2000)
In the phosphorelay signal transduction system for sporulation initiation in Bacillus subtilis, the opposing activities of histidine kinases and aspartyl phosphate phosphatases determine the cell's decision whether to continue with vegetative growth or to initiate the differentiation process. Regulated dephosphorylation of the Spo0A and Spo0F response regulators allows a variety of negative signals from physiological processes that are antithetical to sporulation to impact on the activation level of the phosphorelay. Spo0F∼P is the known target of two related phosphatases, RapA and RapB. In addition to RapA and RapB, a third member of the Rap family of phosphatases, RapE, specifically dephosphorylated the Spo0F∼P intermediate in response to competence development. RapE phosphatase activity was found to be controlled by a pentapeptide (SRNVT) generated from within the carboxy-terminal domain of the phrE gene product. A synthetic PhrE pentapeptide could (i) complement the sporulation deficiency caused by deregulated RapE activity of a phrE mutant and (ii) inhibit RapE-dependent dephosphorylation of Spo0F∼P in in vitro experiments. The PhrE pentapeptide did not inhibit the phosphatase activity of RapA and RapB. These results confirm previous conclusions that the specificity for recognition of the target phosphatase is contained within the amino acid sequence of the pentapeptide inhibitor.